PENGARUH PENGGUNAAN PERMAINAN SCRABBLE DALAM MENINGKATKAN KEMAMPUAN MEMBACA ANAK USIA DINI 5-6 TAHUN - Indriana Ruslan; Syamsuardi; Muhammad Akil Musi; Herlina; Suardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to 1) find out the description of the reading abilities of group B children in village and urban kindergartens 2) find out the application of the Scrabble game to the development of reading abilities of group B children in village kindergartens and urban kindergartens 3) find out the influence of the Scrabble game on the development of group B children's reading abilities B in Village Kindergarten and Urban Kindergarten. The research design uses a true experiment. The data collection techniques used in this research are observation, tests and documentation. The subjects in this research were 10 kindergarteners in the village and 10 kindergarteners in the city. The research results show that there is a significant influence in providing Scrabble games on improving the reading ability of children aged 5-6 years, kindergartens in villages and kindergartens in cities. In Kindergartens in Cities and Rural Areas With results showing that Based on the results of the Friedman test, p-value = 0.000 (p < 0.05), thus H0 is rejected and Ha is accepted, so it is concluded that there is a statistically significant increase between reading ability scores students before and after treatment 1, 2 and 3 using the Scrabble game.